2009
DOI: 10.1097/aog.0b013e3181b6bfdc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increased Body Mass Index on First-Trimester Ultrasound Examination for Aneuploidy Risk Assessment

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…As demonstrated in multiple studies (1519, 54) and visualized herein, maternal obesity decreases the practitioner’s ability to confidently recognize such markers, or accurately assess their dimensions. For example, from the representative images in obese women, please note the poor delineation of the boarders of the lateral ventricles and renal pelvis (which may lead to inaccurate assessment), alongside the decreased echogenicity of the intracardiac echogenic focus (which may lead to missed diagnosis).…”
Section: Figurementioning
confidence: 81%
See 1 more Smart Citation
“…As demonstrated in multiple studies (1519, 54) and visualized herein, maternal obesity decreases the practitioner’s ability to confidently recognize such markers, or accurately assess their dimensions. For example, from the representative images in obese women, please note the poor delineation of the boarders of the lateral ventricles and renal pelvis (which may lead to inaccurate assessment), alongside the decreased echogenicity of the intracardiac echogenic focus (which may lead to missed diagnosis).…”
Section: Figurementioning
confidence: 81%
“…The decreased ability to detect the nuchal translucency in the overweight and obese populations limits effectiveness of first trimester screening for Down syndrome and trisomy 18 (15). Additionally, an increased BMI has been shown to increase the frequency of inadequate nasal bone assessment, increased need for transvaginal ultrasound examination and an increased amount of time to obtain adequate ultrasound images (50, 54). Screening is less effective without a nuchal translucency and studies report up to a 20% failure rate in obtaining a nuchal translucency in morbidly obese populations (49,50).…”
Section: Prenatal Diagnosis: Limitations In An Obese and At Risk Popumentioning
confidence: 99%
“…Given these limitations in the sensitivity and specificity of first‐trimester sonography, our data reinforce the continuing need for second‐trimester anatomic evaluations. Additionally, maternal factors that can limit sonographic examinations, most notably the maternal body mass index and prior abdominal surgery, were not available and could not be factored into the feasibility of detecting limb abnormalities in the first trimester 52 , 53 . Clearly, larger prospective trials are needed to evaluate the assessment of abnormalities on first‐trimester sonography in general and fetal limbs in particular.…”
Section: Discussionmentioning
confidence: 99%
“…In another retrospective study of first-trimester ultrasound, Gandhi et al found an increased ultrasound examination time of 17.01 ± 7.97 min in obese women compared to 15.23 ± 8.09 min in normal-weight women [16]. Although the study did not find obesity to affect the completion rates of obtaining NT, it did find the need to perform transvaginal ultrasound examination to be significantly higher in obese women (41.8%) compared to normal-weight women (22.99%) (P < 0.001).…”
Section: First-trimester Ultrasoundmentioning
confidence: 94%